Language Learning Strategies for Managing Speaking Anxiety among English Students: A Narrative Inquiry - Santiana Santiana; Ningsih Yulianti; Sitti Syakira; Tariq Khan; Supaprawat Siripipathanakul (Institut Agama Islam Negeri Madura, 2026)
Speaking anxiety is one of the most prominent obstacles for EFL students in improving their speaking skills. Successful students use more language learning strategies to overcome their speaking anxiety. This study aims to portray the experiences of an English education department student in dealing with speaking anxiety. More specifically, this study focuses on student’s speaking anxiety experience and the utilisation of language learning strategies. To achieve the objective of the study, a narrative inquiry is employed. The data collection methods are semi-structured interviews and photo elicitation. The interview data was translated into English, re-examined, and analysed using narrative analysis (Labov, 1972). The findings of this study indicate that a student experience speaking anxiety due to several factors, and utilising language learning strategies helped in reducing speaking anxiety itself. The findings of this study are presented in the narrative analysis framework proposed by Labov (1972): (1) Abstract: “The Early Motivation”, (2) Orientation: “A Supportive Environment as the Starting Line”, (3) Complicating action: “Facing Fear in English Speaking”, (4) Resolution: “Strategy Adoption as Emotional Regulation”, (5) Evaluation: “From Avoidance to Agency”, (6) Coda: “Rediscovering Joy in Speaking”. This study suggests applying language learning strategies as it can assist students in coping with speaking anxiety.